Design and Implementation of Plastic Deformation Behavior by Cartesian Impedance Control Based on Maxwell Model - Le Fu; Jie Zhao (Complexity)
Compliance has become one prerequisite of robots designed to work in complex operation environment where dynamic and uncertain physical contact or impact takes place frequently and even intentionally. Impedance control is a typical complaint control methodology. Standard impedance control is based on dynamics described by a spring and damper model connected in parallel way, which endues the robot an elastic behavior. In contrast, plastic deformation can be realized by Maxwell model in which spring and damper connect in series. In this study, a novel Cartesian impedance controller is constructed based on the Maxwell model. Implementation in a robot manipulator is executed to validate and analyze the proposed control law. A plastic deformation behavior of the robot manipulator is produced and certain extent compliance is achieved under the unpredictable impact or contact force exerted by human or other environment objects.